Construction and quantitative evaluation of China’s smart older adults care policy: a PMC-index model approach - Chen, Yuxin; Huang, Yangsen (Frontiers in Public Health, 2025)
Smart older adults care system policies are of great significance for optimizing the allocation of older adults care resources, promoting the innovation and development of smart older adults care system, and effectively responding to population aging. Evaluation of smart older adults care system policy texts can provide theoretical support and decision-making basis for the scientific formulation, effective implementation, adjustment and optimization of smart older adults care system policies. The study analyzes 10 representative policy texts from 72 policies during 2019–2024, and the strengths and weaknesses of each policy and the optimization and adjustment paths are analyzed by calculating the PMC index and drawing PMC surface and radar diagrams. The results show that 3 of the 10 representative policies are assessed as “reasonable and complete,” 6 are rated as “focused,” and 1 is rated as “weak in applicability.” The mean value of PMC index is 7.38. The study shows that the overall design of smart older adults care system policies is scientific, reasonable and of good quality, but there is still room for improvement in many aspects. The performance is as follows: single policy timeliness, short-term policies are more common; diversity of policy aims needs to be enriched; policy content coverage is not comprehensive. Subsequent policies should be improved by focusing on policy timeliness, policy aims and policy content.